Answer:
The expression equivalent to
is
⇒ C
Explanation:
Let us use the exponent rule
=
![a^(m.n)](https://img.qammunity.org/2021/formulas/mathematics/high-school/nee4g4j37i9f1d5u8it943dva55afzo3ku.png)
∵ The expression is
![((m^(5)n)/(pq^(2)))^(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/fhsw8lcj8wn1m4lojrenipsdk7augq6rrz.png)
→ By using the rule above multiply the power of each letter by 4
∵
=
![m^(20)](https://img.qammunity.org/2021/formulas/mathematics/high-school/36h1hd0lvtvjzyd10fsjk3nzj4wpfmgiew.png)
∵
=
![n^(4)](https://img.qammunity.org/2021/formulas/mathematics/college/79dtdazyr691irk6noraavjjj4xiv6clsx.png)
∵
=
![p^(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9c3u36vdf8t8o2dqlkwmxqvn52x1bn1qnl.png)
∵
=
![q^(8)](https://img.qammunity.org/2021/formulas/mathematics/high-school/rsdh96wwzgrkly4f3lokujd9rpiks49ujg.png)
→ Substitute them in the expression above
∴
=
![(m^(20)n^(4))/(p^(4)q^(8))](https://img.qammunity.org/2021/formulas/mathematics/high-school/9e04tjjgt23wgergucxicsguic6w37oa55.png)
∴ The expression equivalent to
is
![(m^(20)n^(4))/(p^(4)q^(8))](https://img.qammunity.org/2021/formulas/mathematics/high-school/9e04tjjgt23wgergucxicsguic6w37oa55.png)